Some family-related factors and personality variables affecting the adjustment of father-absent adolescents - Du-Lagrosa, Milagros E. (Philippine Journal of Psychology, 1986)
This study was inspired by the expressed need to look into the human costs of large scale overseas employment of Filipino fathers, particularly those working in the Middle East. The researcher worked on two major problems: (a) first, she tried to determine whether father's availability (absent or present) and sex of the adolescent influence the adjustment of adolescent children; (b) second, she attempted to identify which among the specified independent variables can significantly predict the adjustment of father-absent adolescents. Findings were based on data obtained from the responses to an Adaptation of the Bell Adjustment Inventory of 160 father-absent and 159 father-present adolescents and from the responses of the mothers of all these adolescents. Two-way analysis of variance was used to answer the first major problem. Results showed that father's availability influenced only the social adjustment of adolescents and that boys differed from girls only in three areas of adjustment - social, emotional and sex role preferences. Multiple regression analysis showed the following as significant predictors of father-absent adolescents: a) for the boys - communication between the absent father and his family, age of the boy at the onset of father-absence, and educational attainment of the father; b) for the girls - communication between the absent father and his family, presence of male model at home, educational attainment of the motehr, sibling position and age of the father.